Evaluation of Virtual Objects: Contributions for the Learning Process - Eleonora Milano Falcão Vieira (Athabasca University Press, 2016)
The constant technological development in education, and the potentiality of the resources offered by Information and Communication Technologies (ICTs), are challenges faced by teaching institutions in Brazil, especially by those institutions, which by the very nature of their services intend to provide distance education courses. In such a scene, one sees the use of technology as a tool to give support and to take part in the process of teaching activities, such as the Virtual Learning Objects (VLOs), which offer an opportunity to contribute to the teaching and learning process. Considering this, the present work aims at analyzing the VLOs used in the distance education courses of Economic Sciences and of Accounting at the Universidade Federal de Santa Catarina (Federal University of Santa Catarina), under the quality criteria indicated by the Learning Object Review Instrument (LORI) methodology proposed by Nesbit, Belfer, and Vargo (2002), Nesbit, Belfer, and Leacock (2004), and Leacock & Nesbit (2007), in order to learn how to better take profit of efforts and resources.